Comparison study between different contrast administration protocols for routine CT thorax examination in two tertiary centres. (June 2019) - Ibrahim, NR; Karim, NK A.; Shuaib, IL; Osman, ND; Hashim, S; Phuah, HF
Abstract: The purpose of this study was to evaluate the degree of contrast enhancement and image quality of computed tomography (CT) thorax examination using different contrast administration protocols. Data was retrospectively collected from 140 patients from two centres; 70 patients (Group A) from Advanced Medical and Dental Institute (IPPT), Universiti Sains Malaysia [19 males, 51 females; mean age ± standard deviation (SD) 53.6 ± 11.2 years; mean weight ± SD 54.04 ± 13.77 kg] using automatic bolus tracking (ABT) with weight-based contrast volume (WBV) administration, and 70 patients (Group B) from Hospital Pulau Pinang (HPP), Ministry of Health Malaysia [24 males, 46 females; mean age ± SD 54.5 ± 13.2 years] using fixed time-delay (FTD) with fixed contrast volume (FV) technique. The degree of enhancement was quantified by measuring Hounsfield unit (HU) values in different arteries and veins, and rated on a 5-point scale (1 = very poor, 5 = excellent) for qualitative assessment. The mean enhancement values in Group B were found to be higher than those in Group A (P < 0.001). There was no statistically significant difference between mean qualitative scores on a 5-point scale in both groups (P = 0.185). A weak correlation was seen between HU values with administered contrast volume (r = 0.1152). Overall, FTD with FV protocol was found to have higher degree of contrast enhancement for routine CT thorax examination. The qualitative assessment showed no significant difference between both protocols although higher mean grading in CT image quality was given by assessors for ABT with WBV technique.